2021
DOI: 10.1177/08874034211001912
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Coordinated Response Toward Nonfatal Strangulation in Facilitating Evidence-Based Prosecution

Abstract: Many states’ laws now classify nonfatal strangulation as part of domestic violence as a felony offense, but prosecution of offenders remains challenging due to the nature of this type of violent offense. This study evaluates a coordinated effort designed to improve one county’s response to nonfatal strangulation. The impact of law enforcement training and specialized forensic medical examinations on facilitating evidence-based prosecution of nonfatal strangulation offenders is examined. Preliminary support is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Additionally, with NFS cases often characterized by little corroborating evidence aside from the victims’ account of the incident [20], we cannot overstate the value of the type of evidence made available when detailed forensic evidence is collected. Research has shown that evidence collection can be improved by training law enforcement to identify and document NFS [16]; however, quality forensic medical documentation is an essential piece as well in holding offenders accountable [11,23–26] and to mitigate serious physical and mental health consequences of NFS [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, with NFS cases often characterized by little corroborating evidence aside from the victims’ account of the incident [20], we cannot overstate the value of the type of evidence made available when detailed forensic evidence is collected. Research has shown that evidence collection can be improved by training law enforcement to identify and document NFS [16]; however, quality forensic medical documentation is an essential piece as well in holding offenders accountable [11,23–26] and to mitigate serious physical and mental health consequences of NFS [2].…”
Section: Discussionmentioning
confidence: 99%
“…A county‐wide training was conducted by the National Family Justice Center Alliance's Training Institute on Strangulation Prevention for those involved in the coordinated effort (i.e., higher ranked law enforcement supervisors, Special Victim Unit agents, prosecutors, health department personnel, victim advocates, and researchers). NFS training included information on lethality, how to recognize the signs and symptoms of NFS, how to identify and understand the anatomy and medical aspects of NFS, how to investigate and present cases for legal proceedings involving NFS, and how to use experts in courts [26]. Training and protocols were also developed to document evidence during a forensic medical examination.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations